2015
DOI: 10.1159/000443539
|View full text |Cite
|
Sign up to set email alerts
|

In Diabetic Kidney Disease Urinary Exosomes Better Represent Kidney Specific Protein Alterations Than Whole Urine

Abstract: Background: Predicting or diagnosing underlying kidney disease by analyzing whole urine remains the mainstay of nephrology practice. However, whole urine is a poor compartment to assess many structural changes in the kidney because whole urine contains only a few proteins derived from the kidney itself. Urinary exosomes, on the other hand, which are derived from the kidney, contain proteins secreted by the kidney. We experimentally tested the hypothesis that ‘urinary exosomes more faithfully represent changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…A greater understanding of kidney MMPs is still needed to better delineate their pathophysiological role in DKD. Although most of these endopeptidases appear to be increased in human DN and apparently related to tubular atrophy and interstitial fibrosis, it is not certain if the activity and concentrations measured in the urine reflect what is really happening in renal tissue or are the consequence of an increased systemic activity [49]. Moreover, it is not yet established if metalloproteinases upregulation precedes fibrosis or if it is a consequence of this lesion.…”
Section: Mmps In Human Diabetic Kidney Diseasementioning
confidence: 99%
“…A greater understanding of kidney MMPs is still needed to better delineate their pathophysiological role in DKD. Although most of these endopeptidases appear to be increased in human DN and apparently related to tubular atrophy and interstitial fibrosis, it is not certain if the activity and concentrations measured in the urine reflect what is really happening in renal tissue or are the consequence of an increased systemic activity [49]. Moreover, it is not yet established if metalloproteinases upregulation precedes fibrosis or if it is a consequence of this lesion.…”
Section: Mmps In Human Diabetic Kidney Diseasementioning
confidence: 99%
“…The majority of studies concerning urinary exosomes have focused on their potential as biomarkers of disease pathology and progression, including prostate and bladder cancers14151617, but their functional significance is now being addressed. Inter-cellular signalling by exosomes in cultured murine renal epithelial cells was demonstrated for the first time by Street et al 18,.…”
mentioning
confidence: 99%
“…[ 13 ] Gudehithlu et al . [ 55 ] found that the measurement of gelatinase in the urinary exosomes was more accurate during the progression of the diabetic nephropathy than the measurement of the whole urine gelatinase. Compared to the whole urine samples, proteins in the urinary exosomes were correlated better with the underlying protein changes in the kidney.…”
Section: Haracteristic Of E Xtracellulmentioning
confidence: 99%